Paradoxical effect of Simian virus 40 enhancer on the function of mouse DNA polymerase beta gene promoter. - Yamaguchi, M (1989)
Simian virus (SV) 40 enhancer (nucleotide position 108 to 294) was combined with chloramphenicol acetyltransferase (CAT) plasmid whose expression is under control of mouse DNA polymerase beta gene promoter. Although the SV40 enhancer stimulated the transient CAT-expression directed by the DNA polymerase beta gene promoter two to three fold in human HeLa cells, it repressed the CAT-expression by 50 to 60% in mouse NIH/3T3 cells. The repression was observed relatively independently on the orientation of the insertion and the distance from the promoter. These properties of the enhancer are very similar to those of so-called transcriptional silencer element. In both HeLa and NIH/3T3 cells, the SV40 enhancer stimulated effectively its own early gene promoter-directed CAT-expression. In mouse immature T-cell line RV-1 in which the SV40 promoter-enhancer did not function, no effect of the SV40 enhancer sequence on the DNA polymerase beta promoter-directed CAT-expression was observed. Thus, it is suggested that both cell type-specific trans-acting factor(s) and the specific combination with the promoter sequence turn the properties of the SV40 enhancer into those of a silencer.